Exosomal Protein Biomarkers in Arthritis: Deciphering the Inflammatory Profiles of RA and OA - Claudia M. Brenis Gómez; Chamaida Plasencia-Rodríguez; Marta Novella-Navarro; Ana Martínez-Feito; Alejandro Balsa; Enrique Calvo-Aranda; Borja Hernández-Breijo (Biomedicines)
Background/Objectives: Rheumatoid arthritis (RA) and osteoarthritis (OA) are highly prevalent diseases and their pathophysiology, diagnosis and treatment continue to be challenging. The aim of this study was to characterize and differentiate the profiles of the serum extracellular vesicles (EVs) isolated from RA and OA patients. Methods: This study included nine patients diagnosed with RA, eight patients with OA during a flare and five healthy controls (HCs). Blood samples were collected and EVs from the serum were isolated for further performance of flow cytometry and proteomic analysis. Results: The extracellular vesicles from HC samples exhibited smaller sizes and were more concentrated than exosomes from RA and OA samples. Surface protein expression was analyzed by flow cytometry. The results showed an enrichment of exosomes derived from antigen-presenting cells in RA samples; this was evidenced by their expression of CD14 and HLA-DR. Proteomic analysis identified 45 differentially expressed proteins between RA and OA patients. Furthermore, Ingenuity Pathway Analysis (IPA) identified inflammatory pathways such as the IL-1β and IL-6 signaling pathways as being enhanced in RA-derived exosomes, while the MYC and ROCK2 signaling pathways were enhanced in OA-derived exosomes. Conclusions: Our results show serum-derived exosomes from RA and OA patients harbor different surface proteins and cargo profiles, mirroring the different pathophysiologic mechanisms underlying these diseases. These results also highlight the promising use of exosomes as disease biomarkers.